Machine design. II : a concise approach - Jauhari, Nitin (New Delhi : CBS Publishers & Distributors, 2016)
Machine Design II : A Concise Approach deals with the design and analysis of mechanical components like gears, bearings, IC engine parts, etc. in a simple and lucid language based on actual classroom interactions. Course content has been planned in such a way that the book (in SI Units) covers the complete course of subject for 6th semester (third year) of UPTU (Lucknow), UTU (Dehradun), GGSIP University (Delhi) and MDU (Rohtak) and most other Indian universities. The book has been written in a simple and easy to follow language, keeping in mind a classroom with both an average student as well as meritorious one, who can grasp the subject basics easily by self study. Each chapter gives to the point design data tables, figures, and concepts along with numerical including problems from previous university examinations. Revision checklist comprising brief summary of specific equations and contents is given at the end so as to have a thorough understanding as well as a quick revision of the subject. Solved university papers along with unsolved problems are included at the end for practice.
Spur gears -- Helical gears -- worm gears -- sliding contact bearings -- rolling contact bearings -- IC engine parts
Includes index.
Keywords: Machine design